IMMERSIVE JOURNALISTIC NARRATIVES (IJNs): language characteristics and strategies for approaching the public - Becker, Beatriz; Munhoz Lago, Andréia (Brazilian journalism research, 2023)
The main language characteristics of immersive journalistic narratives (IJNs) are identified from an exploratory mapping, analyzing a corpus comprising ten IJNs (between 2015 and 2019) that use virtual reality and 360-degree videos. These IJNs were published on YouTube and the official channels of Brazilian information media outlets. This analysis helped us determine that these types of narratives do not focus on the reporter; they instead promote sensory and emotional bonds, thus giving the idea that emotion and empathy are considered to be newsworthiness criteria in contemporary journalistic practices.